1999
DOI: 10.1093/treephys/19.8.481
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization and testing of a biochemically based photosynthesis model for walnut (Juglans regia) trees and seedlings

Abstract: The biochemically based leaf photosynthesis model proposed by Farquhar et al. (1980) and the stomatal conductance model proposed by Jarvis (1976) were parameterized for walnut. Responses of photosynthesis to CO(2) and irradiance were used to determine the key parameters of the photosynthesis model. Concurrently, stomatal conductance responses to leaf irradiance (Q), leaf temperature (T(l)), water vapor pressure deficit at the leaf surface (D), and air CO(2) concentration at the leaf surface (C(s)) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 55 publications
5
65
1
Order By: Relevance
“…Compared with other species, A. chilensis shares some physiological characteristics with shade tolerant species. Stomata of A. chilensis were fully open at values of PPFD around 50 µmol m -2 s -1 , whereas in "heliophilous" species, maximum stomata aperture is reached at values of PPFD of 280-400 µmol m -2 s -1 (Leverenz 1995, Le Roux et al 1999. In addition, light compensation point was comparatively low (10 compared to 16, 23 and 19 µmol m -2 s -1 for P. ponderosa, Pseudotsuga menziesii (Mirb.)…”
Section: Discussionmentioning
confidence: 96%
“…Compared with other species, A. chilensis shares some physiological characteristics with shade tolerant species. Stomata of A. chilensis were fully open at values of PPFD around 50 µmol m -2 s -1 , whereas in "heliophilous" species, maximum stomata aperture is reached at values of PPFD of 280-400 µmol m -2 s -1 (Leverenz 1995, Le Roux et al 1999. In addition, light compensation point was comparatively low (10 compared to 16, 23 and 19 µmol m -2 s -1 for P. ponderosa, Pseudotsuga menziesii (Mirb.)…”
Section: Discussionmentioning
confidence: 96%
“…These authors found that changes in LMA were more important than changes in nitrogen for leaf light acclimation. The control of photosynthetic light acclimation by LMA has been observed for many tree species (Le Roux et al [44,45] and for several shade-tolerant herbaceous species [80]. Comparison of these different results shows that there is no universal rule concerning the relative importance of the factors controlling the light acclimation of photosynthetic capacities.…”
Section: Leaf Functionmentioning
confidence: 99%
“…A-C i curves were used to estimate: (1) V cmax , the maximal rate of RuBP carboxylation, i.e., the potential activity of Rubisco in the absence of limitation by CO 2 availability and photorespiration and (2) J max , the maximal light-driven electron flux. For a detailed description of the equation set, see Le Roux et al (1999). Primary model parameters and their temperature dependencies are listed in …”
Section: Estimating Photosynthetic Capacitymentioning
confidence: 99%